Sari, Eka DESAIN SISTEM PEMINJAMAN PERALATAN KANTOR BERBASIS WEBSITE - Sari, Eka Puspita; Ridwan, Fahri (Universitas Singaperbangsa Karawang, 2024)
Asset management in the company is an important part of ensuring smooth operations and supporting employee performance. However, the lack of a structured lending system often causes problems such as damage, loss of assets, difficulties in monitoring and recording. Those who still use Microsoft Excel are also very vulnerable to input errors and data loss. Therefore this study aims to design and build a website-based information system for borrowing office tools assets that can simplify the process of borrowing assets, improve monitoring of office tools assets, and provide accurate reports regarding borrowing office tools. The system development method used in this study uses the waterfall method, and for system design using UML (Unified Modeling Language). The final results of this study are a website-based office tools asset lending system using the Laravel framework which can facilitate monitoring of the condition and availability of assets, reduce the risk of data loss, and increase the accuracy of reporting.